The application of the theory of reasoned action to school nurses' behaviour - Mullan, Barbara; Westwood, J. (Sage Publications, 2010)
The aim of this paper was to ascertain how valuable the Theory of Reasoned Action (TRA) would be in the prediction of the sexual health education behaviour of school nurses. The current government in the United Kingdom has made a commitment to reducing the high rates of teenage conceptions and sexually transmitted infections and emphasise an increased public health role for school nurses. However, there appears to be no research to suggest that school nurses are the most appropriate healthcare professionals to competently assist with sexual health education in schools. In accordance with the TRA, a questionnaire was designed to measure the intention, attitude, subjective norm and behaviour of the group being surveyed. The purpose-designed questionnaire was distributed to all school nurses in a large geographical area in the United Kingdom. All 46 participants who responded were female (as there are currently no male school nurses in the United Kingdom). No demographic data were obtained as it is believed that the components of the model incorporate all information needed. The major components of the model accounted for 43% of the variance in intention and 46% of the variance in behaviour. Results suggest that the model has good predictive utility in this area and could usefully be employed in interventions with school nurses with the aim of modifying their behaviour. This is the first time the TRA has been used in this context, and it has provided some important information regarding school nurse’s intentions to practise in sexual health.